Development of a 3D model of the home robot and creating promotional video for the project «Home Robot Security» - Savchenko, L.; Vorontsova, D.; Lipovskaya, A. (Theory and practice of design, 2015)
Base don’t he developed sketch in Autodesk Maya software environment created three-dimensional polygonal model home robot guard and its animation, and a promotional video forth e project «Home Robot Security».